2018
DOI: 10.3389/fpsyt.2018.00680
|View full text |Cite
|
Sign up to set email alerts
|

Conflicting Priorities Between Risk Management and Treatment of Schizophrenia in Swiss Forensic Services—A Case Report

Abstract: The Swiss Criminal Code provides measures for mentally-ill offenders focusing on their need for treatment. This may lead to the deprivation of the patient's liberty up to several years. Under certain circumstances the mentally-ill offender can be sentenced to an indefinite incarceration. This case presentation we will describe a forensic psychiatric patient diagnosed with schizophrenia who was ordered an indefinite incarceration in Switzerland after he had been sentenced to 8 years of imprisonment for a delibe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Similar to one study on offender patients with SMI in the Netherlands [ 31 ], but in contrast to a study set in China [ 16 ] and research on non-mentally ill offenders in the US and UK [ 7 , 14 ], present results indicated a higher probability for the female-dominated class to engage in homicide or attempted homicide. Besides cultural aspects, present findings may have been skewed by not including offender patients with SSD waiting in prisons to be transferred into forensic psychiatric treatment [ 55 , 56 ] and who may be more likely to have committed less serious crimes.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to one study on offender patients with SMI in the Netherlands [ 31 ], but in contrast to a study set in China [ 16 ] and research on non-mentally ill offenders in the US and UK [ 7 , 14 ], present results indicated a higher probability for the female-dominated class to engage in homicide or attempted homicide. Besides cultural aspects, present findings may have been skewed by not including offender patients with SSD waiting in prisons to be transferred into forensic psychiatric treatment [ 55 , 56 ] and who may be more likely to have committed less serious crimes.…”
Section: Discussionmentioning
confidence: 99%
“…The judicial system has a difficult role to play in forensic-psychiatric evaluations. It is tasked to ensure the safety of the public, while assuring that the rights of the incarcerated persons are not violated and that they do not suffer undue harm ( 7 ) - described in some legislations as cruel and unusual punishment ( 36 ) or cruel, inhumane and degrading treatment ( 37 ). To ensure a fair process, objectivity is sought in these forensic-psychiatric evaluations.…”
Section: Discussionmentioning
confidence: 99%
“…Forensic assessment informs judicial decisions made to incarcerate the person (i.e., sentence vs. measures, prolongation of measures), (further) treatment, privileges, and release from prisons ( 5 , 6 ). The forensic mental health system is tasked with the role of balancing risk management to avoid future potential harm to others as well as providing treatment to incarcerated persons who suffer from severe mental health illness ( 3 , 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…To exemplify, these implications will be discussed in the areas of criminal law, social law and traffic law in the Swiss juridical system. In criminal law, in particular, release from therapeutic measures according to the Swiss Criminal Code (SCC) is linked to a reduced risk of reoffending [ 62 , 63 ]. Therapy adherence is considered an important variable during risk assessment [ 64 , 65 ].…”
Section: Discussionmentioning
confidence: 99%